Unraveling the taxonomy of the South African mosasaurids - Woolley, Megan Rose; Chinsamy, Anusuya; Caldwell, Michael Wayne (Frontiers in Earth Science, 2022)
Until recently, only one mosasaur was identified in South Africa based on disarticulated skull bones including two dentary fragments and a frontal with articulated elements. These were discovered in 1901 in Pondoland, Eastern Cape and were initially described by Broom in 1912 when he assigned them to Tylosaurus capensis. Aside from this specimen, two other mosasaur remains are known but have remained undescribed and include an isolated muzzle unit and an isolated vertebra. The current study provides a morphological description and taxonomic interpretation of all the mosasaur remains discovered in South Africa. It is suggested that the specimen originally assigned to Tylosaurus is a mosaic of two taxa: A dentary fragment and frontoparietal show affinities with Prognathodon, while a second dentary fragment shows features similar to those of Taniwhasaurus. The muzzle unit presents Prognathodon-like features, and a more recently discovered incomplete vertebra is referred to as an indeterminate Plioplatecarpine. We therefore recognize at least three mosasaur taxa from the Late Cretaceous deposits of South Africa, which we tentatively refer to cf. Prognathodon, cf. Taniwhasaurus, and cf. Plioplatecarpinae. A shark tooth that was embedded in the matrix around the Prognathodon muzzle unit was identified as a Squalicorax pristodontus (Late Campanian to Late Maastrichtian). Strontium analysis of the mosasaur tooth enamel from the same muzzle unit of the cf. Prognathodon material was dated to Late Maastrichtian (87Sr/86Sr = 0.707817; age = 66.85Ma).